DIGITAL APPROACH TO THERMIONIC EMISSION CURRENT TO VOLTAGE CONVERSION FOR HIGH-VOLTAGE SOURCES OF ELECTRONS - Kania, Bartosz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The thermionic emission current is used in many vacuum devices such as evaporators, rare gas excimers, or electron beam objects for high-energy physics. The stability of the thermionic emission current is a very important requirement for the accuracy of those devices. Hence, there is a number of control systems that use a feedback signal directly proportional to the emission current in order to stabilize the thermionic emission current. Most of them use feedback from a high-voltage anode circuit to a low-voltage cathode circuit. However, there is a novel solution that uses linear cathode current distribution and processing of two cathode circuit voltage signals for converting the emission current to voltage. However, it is based on old-fashioned analog technology. This paper shows the thermionic emission current to voltage conversion method with the use of a digital control system. A digital realization of a multiplicative-additive algorithm is presented and proper work in closed-loop mode is confirmed.